2023
DOI: 10.1002/alz.13412
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence for diagnostic and prognostic neuroimaging in dementia: A systematic review

Abstract: IntroductionArtificial intelligence (AI) and neuroimaging offer new opportunities for diagnosis and prognosis of dementia.MethodsWe systematically reviewed studies reporting AI for neuroimaging in diagnosis and/or prognosis of cognitive neurodegenerative diseases.ResultsA total of 255 studies were identified. Most studies relied on the Alzheimer's Disease Neuroimaging Initiative dataset. Algorithmic classifiers were the most commonly used AI method (48%) and discriminative models performed best for differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 222 publications
(381 reference statements)
0
9
0
Order By: Relevance
“…However, studies have shown ML to improve the prediction of risk of other long‐term conditions and related outcomes such as cardiovascular disease 117,118 and suicide, 119 highlighting the ML potential. ML approaches to identify risk markers or factors are already used successfully for analyses of dementia‐related neuroimaging data 71,120 . However, approaches that identify new risk markers/factors temporally preceding the health outcomes would be advantageous, due to the long prodromal period of dementia.…”
Section: Use Of ML To Understand Modifiable Risk Factors For Dementia...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, studies have shown ML to improve the prediction of risk of other long‐term conditions and related outcomes such as cardiovascular disease 117,118 and suicide, 119 highlighting the ML potential. ML approaches to identify risk markers or factors are already used successfully for analyses of dementia‐related neuroimaging data 71,120 . However, approaches that identify new risk markers/factors temporally preceding the health outcomes would be advantageous, due to the long prodromal period of dementia.…”
Section: Use Of ML To Understand Modifiable Risk Factors For Dementia...mentioning
confidence: 99%
“…ML approaches to identify risk markers or factors are already used successfully for analyses of dementia-related neuroimaging data. 71,120 However, approaches that identify new risk markers/factors temporally preceding the health outcomes would be advantageous, due to the long prodromal period of dementia. Such methods have been used previously to detect early metabolite markers as risk factors for type 2 diabetes.…”
Section: Applying Multidisciplinary Approaches From Other Research Fi...mentioning
confidence: 99%
See 1 more Smart Citation
“…This series of eight articles provides a comprehensive overview of current applications of AI to dementia, and future opportunities for innovation to accelerate research. Each review focuses on a different area of dementia research, including experimental models, 7 drug discovery and trials optimization, 8 genetics and omics, 9 biomarkers, 10 neuroimaging, 11 prevention, 12 applied models and digital health, 13 and finally, this article on methods optimization.…”
Section: Introductionmentioning
confidence: 99%
“…Together, this series provides a comprehensive overview of current applications of AI to dementia, and future opportunities for innovation to accelerate research. Each review focuses on a different area of dementia research, including experimental models (this article), drug discovery and trials optimization, 26 genetics and omics, 27 biomarkers, 28 neuroimaging, 29 prevention, 30 applied models and digital health, 31 and methods optimization. 32…”
Section: Introductionmentioning
confidence: 99%